The impact of dynamic social norms messages on motivation to participate in organized colorectal cancer-screening programmes: evidence from an online experiment - Stoffel, Sandro Tiziano; Gao, Jie; Hirst, Yasemin; Von Wagner, Christian (Frontiers in Behavioral Economics, 2025)
BackgroundStudies have shown that presenting information about positive trends in peer behavior can have a greater impact on individual behavior than simply communicating their current behavior. In a web-based experiment, we investigated whether highlighting a positive trend in the uptake of the English bowel cancer screening programme (BSCP) influences the intentions of men and women who initially had low intentions.MethodsWe recruited 1,194 men and women aged 25–49 who had no previous diagnosis of bowel cancer and no experience with the BSCP. These individuals, who had indicated low intentions to participate in screening, were selected from a survey panel. They were randomly assigned to one of four experimental conditions: (1) a control group without a normative message, (2) a group receiving a standard static social norms message communicating current uptake, (3) a group receiving a dynamic social norms message stating that screening participation has been increasing, and (4) a group receiving an extended dynamic social norms message combining a dynamic with a static social norm message. We measured the impact of these messages on their intentions to complete a screening test when invited, their perceived informativeness of the messages, and their active interest in learning more about bowel cancer and the screening test.ResultsNone of the messages influenced intentions in the unadjusted regression; however, the extended dynamic social norms message significantly increased screening intentions compared to the control condition in the adjusted regression. Analysis of changes in intentions before and after the manipulation revealed that both dynamic social norms messages positively influenced changes in the unadjusted regression, while all three messages had a positive impact in the adjusted regression. None of the messages affected active interest or the perceived informativeness of the provided information.ConclusionDynamic social norms messages, which highlight the positive trend in screening participation combined with the current uptake rate have the potential to enhance screening intentions.